Editorial: Fostering sustainable development: Integrating entrepreneurship, Islamic ethics, and community empowerment in contemporary economics - Hendryadi, Hendryadi (LPMP Imperium, 2025)
This edition of Serambi Journal explores sustainable development through entrepreneurship, Islamic ethics, and community economic empowerment. It examines how students develop their entrepreneurial intentions and looks at how digital innovation is changing Islamic philanthropy. Several studies in this edition focus on what drives consumer and member loyalty in halal markets and Islamic cooperatives, highlighting the importance of Sharia compliance, product quality, and trust. The research also addresses financial inclusion strategies, spiritual leadership, and agricultural welfare assessment. Overall, this edition reveals an integrated approach to economic development that aligns traditional Islamic values with modern economic challenges. These studies provide policymakers, educational institutions, and Islamic financial institutions with helpful insights to advance sustainable and ethical economic practices.